Incident portal vein thrombosis in liver transplant recipients in New Zealand: Predictors of risk and validation of portal vein thrombosis risk index calculator - Garg, Paras; Harrison, Barry; Gane, Edward J. (Frontiers in Transplantation, 2022)
The risk of spontaneous portal vein thrombosis (PVT) is increased in patients on the waiting list for liver transplantation and increases perioperative risks. A predictive PVT risk-index (PVT-RI) calculator has been proposed to determine the risk of incident PVT. We performed a retrospective analysis on adult liver transplant recipients at the NZ Liver Transplant Unit between January 1998 and February 2020. Variables reviewed included age at listing and transplantation, wait time from listing to transplant, indication for listing, gender, ethnicity, etiology of liver disease, listing MELD score, hepatocellular carcinoma (HCC), moderate-to-severe ascites, hepatic encephalopathy (>grade 2), transjugular intrahepatic portosystemic shunt (TIPSS), spontaneous bacterial peritonitis (SBP), and diabetes. Incident PVT was determined by imaging of patients while on the waiting list and assessment at transplantation. A total of 553 out of 706 patients met the inclusion criteria. Of those 553, 18 (3.3%) patients had incident PVT. The PVT-RI calculator was not validated in our cohort with only one of those 18 (6%) patients having a score of >4.6 (high risk cut-off score). Longer waiting time for transplant and listing for liver failure rather than HCC were independent predictors of the risk of incident PVT. There was no statistically significant difference in the incidence of PVT in viral vs. non-viral and cholestatic vs. non-cholestatic etiology of chronic liver disease. Patients with longer waiting times on the transplant waiting list should be monitored regularly for PVT.